Pengruh Likuiditas, Solvabilitas, Ukuran Perusahaan, Aktivitas Perusahaan, dan Profitabilitas Terhadap Nilai Perusahaan - Dimas Tegar Maulana; Indra Siswanti (MANAJEMEN, 2026)
This study aims to determine the effect of liquidity, solvency, company size, company activity, and profitability on company value in the telecommunications sub-sector. The sample used was 17 companies in the telecommunications sub-sector listed on the Company stock exchange in 2019-2023. This research method uses a panel data regression data analysis method with the help of the Eviews 13 application, which is used to determine each significant company between dependent companies and independent companies. The sample selection in this study used a purposive sampling method. The data analysis method uses a panel data regression analysis method. This study proves that Liquidity, Solvency, Company Size and Profitability have a positive and significant effect on Company Value. Company Activity does not affect Company Value